Les femmes et le divorce révolutionnaire : de la réception à la construction de la loi (1791-1796) - Laurie Tetaert; Corinne Gomez-Le Chevanton; Vincent Gourdon; Isabelle Robin (Genre & Histoire)
This article reexamines the first legalization of divorce in France through the lens of women’s and family history, building on the work begun at the time of the Bicentenary of the Revolution and that of Suzanne Desan on revolutionary family law and its broad social and political effects. The move towards a secular conception of marriage, as well as its definition as a contract in the Constitution of 1791, in practice opened up the possibility of terminating a marriage. Going beyond divorce statistics, the present study investigates how the law on divorce gave women an opportunity to play a central role in revolutionary events. The study of women's petitions shows concretely how women received and perceived the new legislation, while shedding light on individual situations that were often complex. It also shows that some women managed, in specific circumstances as well as discussing the situation of women in general, to influence the making of the law, bringing the often-abstract legislative text back to down-to-earth considerations.